2007
DOI: 10.1626/pps.10.211
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Twelve Plant Species for Phytoremediation of Petroleum Hydrocarbon-Contaminated Soil

Abstract: : Twelve plant species were screened for their phytoremediation ability for the cleanup of hydrocarboncontaminated soil in Japanese environmental conditions. The plants were cultivated in a greenhouse for 141 days in 1/5000 a Wagner pots containing the experimental diesel-contaminated soil. During plant cultivation, the changes in the total petroleum hydrocarbon (TPH) concentration, soil dehydrogenase activity (DHA) and the number of aerobic bacteria were evaluated. The results of the screening experiment indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(34 citation statements)
references
References 28 publications
1
29
0
4
Order By: Relevance
“…This happened in the contaminated sites because more cracks in 100 to 200µm size range of soil, were produced and thus, over time lead to improve soil quality and increased microbial activity. In another experiment, Kaimi et al (2007), by cultivating twelve plant species measured the changes in total petroleum hydrocarbon concentration, soil dehydrogenase activity and the number of aerobic bacteria and concluded that TPH concentration was more dependent to the soil dehydrogenase activity than to the aerobic bacterial number. Several experiments (Metay et al, 2007;Razafimbelo et al, 2013) showed that crushing soil aggregates would enhance respiration (higher CO 2 ), which results in additional carbon mineralization as SOC pool, physically protected in soil aggregation.…”
Section: Phytoremediation Of Hc and Soil Air Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…This happened in the contaminated sites because more cracks in 100 to 200µm size range of soil, were produced and thus, over time lead to improve soil quality and increased microbial activity. In another experiment, Kaimi et al (2007), by cultivating twelve plant species measured the changes in total petroleum hydrocarbon concentration, soil dehydrogenase activity and the number of aerobic bacteria and concluded that TPH concentration was more dependent to the soil dehydrogenase activity than to the aerobic bacterial number. Several experiments (Metay et al, 2007;Razafimbelo et al, 2013) showed that crushing soil aggregates would enhance respiration (higher CO 2 ), which results in additional carbon mineralization as SOC pool, physically protected in soil aggregation.…”
Section: Phytoremediation Of Hc and Soil Air Statusmentioning
confidence: 99%
“…According to Masakorala (2014) almost all of the acclimated bacterial populations are active and vigorous in most contaminated soils, and especially at the vicinity of soil-root rhizosphere. As mentioned by Kaimi et al (2006), Jing et al (2007) and Kaimi et al (2007), rhizosphere (important interface of soil and plant), is an important area which plays a vital role in phytoremediation of contaminated soils (Maletić et al 2013). At the rhizosphere area microorganisms positively affect heavy metal mobility and thus to the availability of the ions for the plants by different mechanisms.…”
Section: Phytoremediation Of Hc and Soil Organic Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…Багато з них пропонують використовувати трав'янис-ті рослини зі злакових [49][50][51][52]. Повідомляється, що головною перевагою трав є їх велика волокниста ко-ренева система, яка має велику площу поверхні коре-ня, порівняно з іншими видами, а також може прони-кати у ґрунт на глибину до 3 м [40,49].…”
Section: методи фіторемедіації нафтозабруднених грунтівunclassified
“…In the presence of PW, the growth of bacteria, actinobacteria and ryegrass possess a synergistic effect. The roots are known to release root exudates, such as amino acids, sugars, enzymes and complex carbohydrates, providing carbon source and energy for the growth of rhizosphere microorganisms (Kaimi et al, 2007;Phillips et al, 2012;Sun et al, 2010). Parrish et al (2005) reported that the PAH-degrading microbial population in vegetated treatments were much higher than those in unvegetated controls after 12 months of plant growth, the same tendency was also found in our research, the number of bacteria and actinobacteria increased by the rhizosphere effect, meanwhile treatment inoculate with PW also possess a higher level of microbe in some extent.…”
Section: Table1mentioning
confidence: 99%